Figures 10-11 from: Zan ND, Sarbini A, Taha H, Tan IV, Azri A, Kahar R, Metali F, Ahmad N, Arai T (2020) Occurrence and ecological implication of a tropical anguillid eel, Anguilla marmorata, in Brunei Darussalam, Borneo Island. Zoologia 37: 1-7. https://doi.org/10.3897/zoologia.37.e39468 - Zan, Nur Dhabita; Sarbini, Ain; Taha, Hussein; Tan, Iy Vonne; Azri, Azie; Kahar, Rafhiah; Metali, Faizah; Ahmad, Norhayati; Arai, Takaomi (Zenodo, 2020)
Figures 10-11 Phylogenetic maximum likelihood tree using the mtDNA COI of Anguilla marmorata and other Anguilla species from the GenBank database with indicated accession numbers (10). Serrivomer sector was used as outgroup. The bootstrap proportions are shown next to the branches. Scale refers to evolutionary distance and in the unit of number of base substitutions per site. Haplotype network constructed with Anguilla marmorata mtDNA COI sequences (11). Each colour represents a sample site. The size of the circle is proportional to the number of samples that belong to each haplotype. Different haplotypes are labelled as H1 to H11. Each dash, which appears on the line that connects two haplotypes together, symbolizes one mutational step.